Factors shaping inter-organizational trust in e-commerce based on literature review - Gajda, Klaudia (Zielona Góra: Faculty of Economics and Management Press)
The article is devoted to identifying external and internal factors that shape inter-organizational trust in e-commerce. Studying how trust between e-commerce partners is built, four key B2B trust spheres were analyzed based on literature.
Keywords: e-comerce; inter-organizational; trust; external factors; internal factors; B2B; handel elektroniczny; międzyorganizacyjność; zaufanie; czynniki zewnętrzne; czynniki wewnętrzne